Análisis de una metodología de seguridad informática para el desarrollo de aplicaciones móviles usando herramientas Open Source. - Gómez Coello, Kiara Michelle (2023)
By applying an information security methodology, we contribute to improving the security of mobile applications, thereby avoiding vulnerabilities that may be exploited by malicious users or hackers. If mobile applications development is not done with care and attention, there is a risk that a cyber attacker may access confidential information or, in the worst case scenario, control the application. The use of Open Source security tools provides transparency and confidence to users, which increases the use of the application and reduces the risk of attacks. The OSSTMM methodology allows us to perform penetration testing and security evaluation on information and technology systems. This methodology is divided into five areas that allow us to gather the current state of mobile applications.